How Psycholinguistics and Social Factors Influence SLA on Elementary and Secondary Students in Indonesia - Ratna Sari Dewi; Siti Zulfa; Yatni Fatwa Mulyati; Dhila Nurul Azmi; Tresna Nur Andini; Rifdatul Habibah; Wiwi Rhamadina (Universitas Pahlawan Tuanku Tambusai, 2022)
Psycholinguistic factors are part of internal factors which connect to the intellectual process. Social factors are part of external factors which connect to social interactions. This study aims to reveal the psychological and social factors in second language acquisition of elementary and secondary students in Indonesia. The research employs a qualitative methodology focused on library research. The data used documentation techniques to gather and analyse the data through the descriptive approach. Documentation data reveal that there are five psycholinguistic factors such as (1) attitude, (2) aptitude, (3) motivation, (4) personality qualities, and (5) biological processes. Also, this research found eight social factors such as (1) gender, (2) age, (3) social class, (4) motivation, (5) attitude, (6) cultural process, (7) students' characters and situation, and (8) economic status. No particular factor can be stated as dominant among psycholinguistic and social factors. Therefore, this research reveals the same element that occurred in psycholinguistic and social factors: motivation and attitude. This study suggests that teachers should pay extra attention to students' motivation and attitude since it relates to psychological and social factors, which could support their second language acquisition.